Utilização da bagana de carnaúba como cobertura vegetal para redução do consumo de água em hortaliças irrigadas - Almeida, Antônio Vanklane Rodrigues de (2019)
In regions with limited water resources, such as Brazilian semi-arid, the efficient use of water becomes indispensable every day for irrigated agricultural production in this region. In this sense, the objective of this research was the agroeconomic evaluation of the effect of water production factors and soil cover levels of the carnauba bagana of the comet radish and coriander cultures. The research was conducted in the period from April to August of 2018 in two production cycles in area belonging to Prece (Cooperative Cell Education Program), located in the municipality of Pentecoste-CE. The experiment was conducted in a randomized block design with four replicates. The treatments consisted of five irrigation slides (50%, 75%, 100%, 125% and 150% of the daily reference evapotranspiration, ETo) and five different levels of mulch made up of carnauba bagana: 25%; 50%; 75%, 100% and soil without cover 0%, totalizing 100 experimental plots. The results allowed to conclude that the carnauba bagana had potential for use as mulch in the cultivation of radish and coriander. The maximum efficiency was verified on the 50% ETcloc blade with 100% bagana coverage, where water efficiency of 7.85 kg m-3 was reached for radish and 94.40 kg m-3 for culture of coriander. It was verified that the maximum productivity of the coriander verdade was obtained with the application of a blade of 101.8 and 112.3 mm in the first and second cycle respectively, applying 50% of soil cover with bagana and for the maximum productivity of the radish was obtained with the application of a blade of 99.4 and 77.3 mm in the first and second cycle respectively, applying 100% soil cover with bagana.